A new personalized vaccine strategy based on inducing the pyroptosis of tumor cells in vivo by transgenic expression of a truncated GSDMD N-terminus - He, Jinrong; Zheng, Peng; Chen, Yongjun; Qi, Jialong; Ye, Chao; Li, Duo; Yang, Ying; Yang, Ying; Liu, Qingwen; Hu, Yongmao; Zheng, Xiao; Li, Weiran; et al. (Frontiers in Immunology, 2022)
The variability and heterogeneity of tumor antigens and the tumor-driven development of immunosuppressive mechanisms leading to tumor escape from established immunological surveillance. Here, the tumor cells were genetically modified to achieve an inducible overexpression of the N-terminal domain of gasdermin D (GSDMD-NT) and effectively cause pyroptosis under a strict control. Pyroptotic tumor cells release damage-associated molecular patterns (DAMPs) and inflammatory cytokines to promote the maturation and migration of bone marrow-derived dendritic cells (BMDCs). Furthermore, local tumor delivery, and preventive or therapeutic subcutaneous immunization of the modified cells, followed by the induction of GSDMD-NT expression, significantly stimulated both the systemic and local responses of antitumor immunity, and reprogrammed the tumor microenvironment, leading to the dramatic suppression of tumor growth in mice. This study has explored the application potency of inducing the pyroptosis of tumor cells in the field of tumor immunotherapy, especially for developing a new and promising personalized tumor vaccine.